PERAN DONGENG BAGI PERKEMBANGAN DAN PEMBENTUKAN KEPRIBADIAN ANAK - Ipriansyah Ipriansyah (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2011)
Various forms of folklore such as fairy tales are almost extinct because they are less popular compared to some TV shows. Even though various forms of folklore are only a fewbut it teaches positive values that are useful for children's development. Tale, for example, is believed to have an important role in helping cognitive development such as language, thought, and sosioemosional of a child such as emotions and personality. A fairy tale is quite reasonable to have an important role toward the development of children. Development is a pattern of change as a result of biological, cognitive, and sosioemosional processes which has begun from the time of conception until the rest of a lifetime .Among periods of human development, there is a phase of human development which refers to the storytelling phase, that is when a child is in the age of 5 to 8 years.